18F-Fluorocholine PET and 4D-CT in Patients with Persistent and Recurrent Primary Hyperparathyroidism - Adrien Latge; Sophie Riehm; Michel Vix; Jacob Bani; Mihaela Ignat; Valentin Pretet; Mehdi Helali; Giorgio Treglia; Alessio Imperiale (Diagnostics, 2021)
Patients with primary hyperparathyroidism (pHPT) can develop persistent (P-pHPT) or recurrent (R-pHPT) disease after parathyroidectomy. Before recommending reoperation, recurrence must be accurately identified because of the high risk of complications. Our study evaluates 18F-fluorocholine (18F-FCH) PET/CT and 4D-CT integrated in PET/4D-CT in patients with P-pHPT/R-pHPT. Patients with P-pHPT/R-pHPT investigated by 18F-FCH PET/4D-CT between May 2018 and March 2021 were retrospectively included. Forty-two patients were included, 37 of whom underwent 4D-CT. The sensitivity and detection rate (DR%) were 95% and 88% for 18F-FCH PET/CT and 70% and 63% for 4D-CT, respectively. PET/CT and 4D-CT were concordant in 18/24 glands and concordant and positive in 15/24 (63%) glands. Discordant results were obtained for 6/24 glands. The surgical success rate was 65%. PET/CT showed significantly higher sensitivity than 4D-CT. Dynamic CT allowed the identification of no additional glands missed by PET/CT, and the combination of the 2 techniques did not improve the sensitivity or DR%. 18F-FCH PET/CT appears to be a valuable technique to accurately detect hyperfunctioning parathyroid tissue in patients with P-pHPT/R-pHPT and is better than 4D-CT. Except for cases with doubtful locations of PET targets that may require 4D-CT for surgical guidance, standard nonenhanced 18F-FCH PET/CT can be effectively recommended in patients with P-pHPT/R-pHPT before reoperation.